2002
DOI: 10.1207/s15326977ea0802_04
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Abilities and Motivational Processes in High School Students' Situational Engagement and Achievement in Science

Abstract: Building on Snow's (1989) idea of 2 pathways to achievement outcomes, a performance and a commitment pathway, this study examined how cognitive and motivational factors associated with each of these pathways, respectively, contributed to the prediction of achievement outcomes in science. The sample consisted of 491 10thand 11th-grade high school students. Results of hierarchical regression analyses showed that (a) students' cognitive abilities were the strongest predictors of their performance in science as me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
110
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(125 citation statements)
references
References 25 publications
10
110
0
5
Order By: Relevance
“…We thought that the female participants in the experiment would mainly fall in the latter category and, therefore, would benefit more than the males from motivational scaffolding. In line with other research on self-efficacy in science (e.g., Catsambis 1995;Lau and Roeser 2002;Mattern and Schau 2002;Osborne et al 2003;Yeung et al 2010), the girls in our study were found to start with significantly lower self-efficacy than the boys. However, the data further showed that the absolute level of these appraisals left room for improvement for both boys and girls.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We thought that the female participants in the experiment would mainly fall in the latter category and, therefore, would benefit more than the males from motivational scaffolding. In line with other research on self-efficacy in science (e.g., Catsambis 1995;Lau and Roeser 2002;Mattern and Schau 2002;Osborne et al 2003;Yeung et al 2010), the girls in our study were found to start with significantly lower self-efficacy than the boys. However, the data further showed that the absolute level of these appraisals left room for improvement for both boys and girls.…”
Section: Discussionsupporting
confidence: 92%
“…Another factor is that motivation affects learning only indirectly. It is a mediator that influences facets of task engagement such as goal setting, task choice, effort, and persistence (e.g., Järvelä et al 2008;Lau and Roeser 2002;Vollmeyer and Rheinberg 2006). In turn, these mediators influence learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When we extend this segment we also see a social persuasion opportunity unfolding for Gina in the final lines of the segment (turns [23][24][25][26][27][28][29][30][31][32][33]. She may remember Lisa's interruption later and judge her ability to write the expression for displacement from an area under the curve based upon this experience.…”
Section: B Social Persuasion Opportunitiesmentioning
confidence: 96%
“…Studies have shown that self-efficacy is able to predict a university student's persistence in science majors as well as science career choices [9,10,13,14,16]. Additionally, researchers have found that self-efficacy can predict achievement in science for high school students [24,25] and university students [8][9][10][11][12]. At Florida International University, an hispanic-serving institution in the southeastern United States, we have also found that a student's self-efficacy in physics at the beginning of an introductory physics course predicts the likelihood of a student passing that same course [26].…”
Section: Previous Research On the Development Of Self-efficacymentioning
confidence: 99%